TOURISM SATELLITE ACCOUNT A STATISTICAL TOOL TO ANALYSE TOURISM ROLES - Ida Bagus Made Wiyashya (JURNAL KEPARIWISATAAN, 2004)
This article tries to explore the Tourism Satellite Account (TSA) results in severalcountries. It is a statistical tool used to derive tourism multiplier in a country'seconomy. In preparing a TSA an input-output model is applied. Resultsshow differences in tourism roles in a country's economy due to the sizeand leakage in tourism